2019
DOI: 10.1001/jamainternmed.2019.2431
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Patients With Atrial Fibrillation Receiving a Direct Oral Anticoagulant

Abstract: IMPORTANCE Patients with atrial fibrillation (AF) who use a direct oral anticoagulant (DOAC) and request elective surgery or procedure present a common clinical situation yet perioperative management is uncertain. OBJECTIVE To investigate the safety of a standardized perioperative DOAC management strategy. DESIGN, SETTING, AND PARTICIPANTS The Perioperative Anticoagulation Use for Surgery Evaluation (PAUSE) cohort study conducted at 23 clinical centers in Canada, the United States, and Europe enrolled and scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
402
3
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 345 publications
(427 citation statements)
references
References 42 publications
11
402
3
11
Order By: Relevance
“…Therefore, we do not recommend measuring DOAC drug levels prior to dental extractions to predict bleeding outcomes. Our findings support the current practice of standardized perioperative DOAC management based on the drug’s pharmacokinetic properties and type of surgical procedure, rather than drug levels …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, we do not recommend measuring DOAC drug levels prior to dental extractions to predict bleeding outcomes. Our findings support the current practice of standardized perioperative DOAC management based on the drug’s pharmacokinetic properties and type of surgical procedure, rather than drug levels …”
Section: Resultssupporting
confidence: 77%
“…Our findings support the current practice of standardized perioperative DOAC management based on the drug's pharmacokinetic properties and type of surgical procedure, rather than drug levels. 19,20 We recognize that this study has a number of limitations. First, as the sample size of each cohort was limited to the eligible patients who presented to our department and provided informed consent, sample size calculations were not performed.…”
Section: Ta B L E 1 Patient and Procedural Characteristicsmentioning
confidence: 96%
“…19 More recently, preliminary results from the large, multicenter PAUSE trial assessing standardized DOAC interruption for an elective procedure or surgery also found a 30-day MB rate of 1.43% (95% CI: 0-1.83). 24 The bleed risk stratification of procedures and surgeries requiring OAC interruption into non-high bleed risk vs high bleed risk is important because the anticipated background event rates for bleeding would anchor the timing of periprocedural OAC management. Based on early available data of background postprocedural bleed rates, it was suggested that the 2-day risk of MB in patients on chronic OAC without heparin bridging therapy was 0%-2% in low bleed risk procedures and 2%-4% in high bleed risk procedures.…”
Section: Pro Cedur Al /Surg I C Al B Leed Ris K S Tr Atifi C Ati Onmentioning
confidence: 99%
“…25 Recent data from the PAUSE Trial with DOACs reveal that for low/ moderate bleed risk procedures the 30-day MB incidence was 0.9% (95% CI: 0-1.3), while that of high bleed risk procedures or surgeries was 2.48% (95% CI: 0-3.4). 24 For surgeries/procedures classified in the low/moderate bleedrisk category, a strategy of OAC interruption of two to three halflives preprocedure, which would enable some residual anticoagulant effect (ie 3 days off for warfarin, 1 day off for DOACs) and therapeutic-dose anticoagulant resumption within 1 day postprocedurally (for heparin bridging therapy with warfarin and for DOACs in general) would be associated with an acceptably low periprocedural bleeding risk. For procedures/surgeries in the high bleed-risk category, a strategy of OAC interruption of four to five half-lives preprocedure (ie, 5 days off for warfarin and 2 days off for DOACs), and resumption 2 to 3 days postprocedurally in the case of treatment-dose UFH or LMWH bridging therapy for warfarin and for DOACs in general would be associated with an acceptable periprocedural bleeding risk.…”
Section: Pro Cedur Al /Surg I C Al B Leed Ris K S Tr Atifi C Ati Onmentioning
confidence: 99%
“…Permanent or temporary antithrombotic therapy is increasingly prescribed with the aging of the population in industrialized countries. Approximately 1 in 6 patients will require perioperative anticoagulation management including urgent surgery every year 1 . Furthermore, about 1% of the patients need treatment for acute DOAC‐associated bleeding 2 .…”
Section: Introductionmentioning
confidence: 99%